Pola Menstruasi, Gaya Hidup dan Dukungan Keluarga Berhubungan dengan Kejadian Anemia - Retno Sugesti; Dian Islami; Madinah Munawaroh (MPI Press, 2021)
Introduction: Anemia is a condition where there has been a shortage of red blood cells in the body with HB levels less than 12 g/dl. Menstrual patterns, lifestyle, and family support are some of the risk factors for anemia in adolescent girls. Objective: This study aims to determine the relationship between menstrual patterns, lifestyle, and family support with the incidence of anemia in adolescent girls at Gema Islami Middle School, Tangerang Regency in 2021. Method: This research uses a descriptive-analytic with cross-sectional approach. The population of this study amounted to 38 students and the sampling technique used was total sampling with a sample of 38 students. Result: The results of this study indicate that there is a significant relationship between menstrual patterns and the incidence of anemia, the p-value is 0.006 and the results are OR = 7,500 (1,626-34,591), lifestyle with the incidence of anemia, the p-value is 0.026 and OR = 5,200 (1,149-23,540). and family support with the incidence of anemia obtained a p-value of 0.013 and the result of OR = 6.222 (1.365-28.369). Conclusion: Menstrual pattern, lifestyle, and family support are related to the incidence of anemia, and of the 3 independent variables, the menstrual pattern variable is the variable most related to the incidence of anemia in adolescent girls at Gema Islami junior high school Tangerang in 2021.